Agriculture causes homogenization of plant‐feeding nematode communities at the regional scale. Issue 12 (22nd September 2021) - Archidona‐Yuste, Antonio; Wiegand, Thorsten; Eisenhauer, Nico; Cantalapiedra‐Navarrete, Carolina; Palomares‐Rius, Juan E.; Castillo, Pablo
Abstract: An emerging research line in conservation ecology addresses how environmental change drivers may cause the biotic homogenization of ecological communities by shifts in species diversity and community composition. While the drivers have been explored in unmanaged ecosystems and managed agricultural systems, this issue has received limited attention in regard to a key soil bioindicator organisms, soil nematodes. In this study, we evaluated the effect of land‐use change and intensification on the diversity of plant‐feeding nematodes (PFN) though taxonomic and functional measures of alpha and beta diversity. We selected olive tree farms in southern Spain as the study system, given the wide distribution of wild forms in unmanaged systems and cultivated forms in agricultural systems, thus providing the opportunity to assess the effects of land‐use intensity. Notably, our study revealed that the conversion from natural to agricultural systems and even moderate increases in land‐use intensity caused a significant biotic homogenization by enhancing the functional similarities of PFN communities. Our study emphasizes the key role of body size in structuring nematode communities in response to land‐use type and intensity. Synthesis and applications . The importance of soil nematodes in soil processes is well known. We show that land‐use intensification reduces soil nematode diversity. Our study has important implications for the development of management strategies that foster soil biodiversity conservation such as no or minimal tillage and logging, vegetative covers and the maintenance of natural habitat. Abstract : The importance of soil nematodes in soil processes is well known. We show that land‐use intensification reduces soil nematode diversity. Our study has important implications for the development of management strategies that foster soil biodiversity conservation such as no or minimal tillage and logging, vegetative covers and the maintenance of natural habitat. Resumen: Esta es una línea de investigación emergente en ecología de conservación que aborda cómo los cambios ambientales pueden influir en la homogenización biótica de comunidades ecológicas mediante cambios en la diversidad de especies y en la composición de la comunidad. Sorprendentemente, este problema ha recibido una atención limitada en organismos del suelo, como son los nematodos del suelo. En este estudio, se evalúa el efecto del cambio de uso del suelo y su intensificación sobre la diversidad de nematodos fitoparásitos (NF) a través de la estimación taxonómica y funcional de la diversidad alfa y beta. Para ello, seleccionamos el olivar del sur de España como sistema de estudio ya que la amplia distribución de formas silvestres y cultivadas ofrece una oportunidad única de observar los efectos de los continuos aumentos en la intensidad del uso del suelo entre los bosques naturales y los sistemas agrícolas intensivos. En particular, nuestro estudio reveló que la conversión de sistemas naturales a agrícolas, e incluso aumentos moderados en la intensidad del uso del suelo, causaron una homogeneización biótica significativa al mejorar las similitudes funcionales de las comunidades de NF, representadas por el tamaño del cuerpo de los nematodos. Síntesis y aplicaciones. Nuestro estudio tiene importantes implicaciones para la conservación de la biodiversidad del suelo a través de prácticas de manejo que abarcan el mínimo o nulo laboreo, el uso de cubiertas vegetales y el mantenimiento natural del hábitat.